Schooling of Students with Intellectual Disabilities: Family and School Perspectives - Maturana, Ana Paula Pacheco Moraes; Mendes, Enicéia Gonçalves; Capellini, Vera Lúcia Messias Fialho (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, Programa de Pós-Graduação em Psicologia, 2019)
Abstract Educational policies aimed at school inclusion have led to an increased enrollment of students with special education needs (SEN) in mainstream schools and, as a result, there is an increase in transfers from specialized institutions to mainstream schools. This study analyzed the perspectives of school professionals and family members on school transfers of students with intellectual disabilities (ID). Six family members and ten school professionals participated in the study. All attended semi-structured interviews, whose analysis allowed us to identify five thematic axes: teacher training; lack of preparation and information; lack of supports; lack of preparation for transfer; expectations regarding the ID student, mainly concerning behavioral characteristics, learning and performance. Results confirm data from research on the implementation of special education in inclusive environments, indicating that teachers’, managers’ and families’ conceptions of inclusion depend on the severity of the student’s disability, and on the skills and attitudes of the professionals.

Resumen Las políticas educativas hacia la inclusión escolar están aumentando las matrículas de alumnos, público objetivo de la educación especial, en la escuela común, y como consecuencia se observa un incremento de transferencias de las instituciones especializadas para las escuelas comunes. El estudio analizó las perspectivas de profesionales de la escuela y de familiares sobre las transferencias escolares de alumnos con discapacidad intelectual (DI). En él participaron seis familiares y diez profesionales de la escuela. Todos los participantes respondieron a una entrevista semiestructurada, cuyo análisis permitió identificar cinco ejes temáticos: la formación del profesor, falta de preparación y de información; la ausencia de soportes; la ausencia de preparación para la transferencia; las expectativas en cuanto al alumno con DI en relación a las características conductuales, de aprendizaje y de desempeño. Los resultados confirman datos presentes en investigaciones sobre la implementación de la educación especial en ámbitos inclusivos, señalando que las concepciones de los profesores, gestores y familiares frente a la inclusión dependen de la severidad de la discapacidad del alumno, de las habilidades y actitudes de los profesionales.

Resumo Políticas educacionais voltadas à inclusão escolar têm levado ao aumento de matrículas de alunos público alvo da educação especial (PAEE) na escola comum e como resultado observa-se aumento de transferências das instituições especializadas para escolas comuns. O estudo analisou as perspectivas de profissionais da escola e familiares sobre as transferências escolares de alunos com deficiência intelectual (DI). Participaram seis familiares e dez profissionais da escola. Todos responderam a uma entrevista semiestruturada, cuja análise permitiu identificar cinco eixos temáticos: formação do professor, despreparo e falta de informação; falta de suportes; ausência de preparo para a transferência; expectativas quanto ao aluno com DI em relação às características comportamentais, aprendizagem e desempenho. Os resultados ratificam dados presentes em pesquisas sobre a implementação da educação especial em ambientes inclusivos, sinalizando que concepções dos professores, gestores e familiares frente à inclusão dependem da severidade da deficiência do aluno, das habilidades e atitudes dos profissionais.
La Escolarización de Alumnos con Discapacidad Intelectual: Perspectivas de la Familia y de la Escuela
Escolarização de Alunos com Deficiência Intelectual: Perspectivas da Família e Escola
Keywords: inclusion; special education; intellectual disability; school transference; inclusão escolar; educação especial; deficiência intelectual; transferência escolar